Immigration and unemployment in Europe: does the core-periphery dualism matter? - Piero Esposito; Stefan Collignon; Sergio Scicchitano (Global Labor Organization (GLO), 2019)
In this paper, we assess the impact of immigration and unemployment for a sample of 15 EU countries between 1997 and 2016. We test for the existence of a core-periphery dualism based on differences in macroeconomic fundamentals and labour market characteristics. We use a Panel Error Correction Model to assess the direction and persistence of the impact of immigration on domestic unemployment in the short and in the long run. In the long run, immigration is found to reduce unemployment in all peripheral-countries. In core countries, we find no long-run impact of immigration on unemployment due to substantial heterogeneity. As for short-run dynamics, we find a confirmation of the result that immigration reduces unemployment for the whole sample. Based on differences in employment protection and activity rates, larger impacts are found for Scandinavian and Anglo-Saxon countries, while lower and less significant impacts are found for Italy, Greece and Portugal.
Keywords: C23; E23; F22; J61; 330; International Migration; Unemployment; European Union; Panel Data